Disparities in food insecurity at the intersection of race and sexual orientation: A population-based study of adult women in the United States. (December 2020) - Patterson, Joanne G.; Russomanno, Jennifer; Teferra, Andreas A.; Jabson Tree, Jennifer M.
Abstract: Food insecurity affects 1 in 8 American adults annually, and is more prevalent in Black and sexual minority women. We applied an intersectional approach to investigate food insecurity prevalence in women with intersecting minority race and sexual orientation. We used two United States surveillance systems—National Health Interview Survey (NHIS) 2013–2018 and National Health and Nutrition Examination Survey (NHANES) 2005–2014, to estimate how race and sexual orientation jointly influence food insecurity prevalence in women aged 18–59 years (NHIS: N = 47596; NHANES: N = 5106). All analyses were stratified for Supplemental Nutrition Assistance Program (SNAP) use. Relative measures estimated weighted prevalence ratios (PR) comparing Black and White sexual minority women (SMW) to heterosexual White women. Absolute prevalence measures estimated the excess prevalence of food insecurity due to multiple marginalization. Patterns of food insecurity prevalence were similar across NHIS and NHANES, and differed only for non-SNAP users. Relative prevalence of food insecurity was greater in Black SMW than heterosexual White women in NHIS (PR: 2.16; 95% confidence interval [CI], 1.41–3.30) and NHANES (PR: 2.79; 95% CI, 1.73–4.51). The strength of the association between multiple marginalization and food insecurity was stronger for Black SMW than White SMW. Absolute measures were significant only for NHIS and did not support our a priori hypothesis: For non-SNAP users, being Black and sexual minority reduced the joint disparity in food insecurity by approximately 50% (Synergy Index: 0.52; 95% CI, 0.11–0.93). Overall, our study illuminated population-level differences in food insecurity among women of diverse minority races and sexual orientations. Black SMW experienced high rates of food insecurity, which may contribute to chronic disease disparities. Yet, intersecting minority social positions (race and sexual orientation) reduced food insecurity; these findings are unexpected and must be further investigated. Increasing SNAP use among multiply marginalized women may attenuate food insecurity disparities. Highlights: Intersectional methods are needed to quantify food insecurity disparities. Black SMW were more than 200% as likely to report food insecurity. White SMW were 81–87% as likely to report food insecurity. SNAP use attenuated food insecurity disparities for multiply marginalized women. Joint effects of race and sexual orientation reduced food insecurity prevalence.